URGENSI MUFTI PEREMPUAN DI DUNIA KONTEMPORER PERSPEKTIF MUBADALAH DAN GENDER - Hidayat, Muhammad Syarif (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
The mufti's position in society is very important in responding to the problems of the people. Moreover, in this contemporary era where science and technology are developing so rapidly. However, many women's problems do not receive serious attention. This research is intended to find out what is the position and involvement of women in a fatwa institution or becoming a mufti. How important its role is in the contemporary world is seen from the perspective of gender and gender. This research uses qualitative methods with a type of library research related to several related literature. This research also uses thematic analysis to identify the main themes that emerge from the data that has been collected. From this research, it is known that there is no provision or requirement that a mufti must be a man so that women who have adequate qualities and capabilities are worthy of being a mufti. Apart from that, the presence of female muftis in the contemporary era is very important to ensure gender justice in society, apart from being an enlightener and provider of solutions to people's problems, especially those related to women's issues. With an effective empowerment strategy, it is hoped that female muftis can make a major contribution to realizing more equal gender justice in society.